Mutually transformative missions: A postcolonial, process-relational Pentecostal missiology. (July 2015) - Reichard, Joshua D.
This article comprises a development of Amos Yong's three-phase Pentecostal missiology in the direction of postcolonialism fostering "mutually transformative missions." An appropriation of theological insights from process-relational theology and a creative application of those insights to Yong's postcolonial proposal facilitate a fuller "non-colonial" missiological model that is grounded both metaphysically and theologically. Three particular metaphysical categories from process-relational theology may support the development of a postcolonial Pentecostal missiology: panentheistic pluralism, mutual transformation, and divine vulnerability. Two case studies are presented to highlight these themes. In terms of metaphysical grounding, process-relational theology may aid Pentecostals in freeing themselves of their colonial rootedness, not just in the West, but in the burgeoning Pentecostal movements in the Global South. By embracing panentheistic pluralism, mutual transformation, and divine vulnerability, Pentecostal missiology might take another step in the postcolonial direction. In so doing, Pentecostals might ultimately articulate a global non-colonial, process-relational missiology that focuses less on coercive conquest and more on loving relationality.